دور التحول الرقمي في تحسين جودة التدقيق في ظل جائحة كورونا (COVID 19) - دراسة استطلاعية لأراء عينة من المدققين الخارجيين-: The Role of Digital Transformation in Improving Audit Quality in Light of The Corona Pandemic (COVID 19) An Exploratory Study of The Opinions of a Sample of External Auditors - عبد الحق زيـــاني; خَيِّرَة مجدوب (Journal of North African Economies, 2025)
The purpose of this study is to shed light on the role of digital transformation in improving audit quality and efficiency in the face of the spread of the COVID-19 pandemic by leveraging digital transformation to protect the privacy of financial data and accounting data and enhance their security, as well as its ability to save time and reduce the cost of audit procedures. In order to achieve the set objectives and complete the theoretical aspects, primary data on the research topic were collected through questionnaires and subsequently transcribed and analyzed using the SPSS program and processed using appropriate statistical tests to obtain results that support the trend of greater use of multiple digitalization’s Transforming technology to improve quality and performance in the accounting profession. By distributing the questionnaire to 180 external auditors to investigate their opinions. The study concluded with a set of results that enhance interest in moving towards applying digital transformation technologies such as artificial intelligence, cloud computing, robotics, etc., maximizing the quality of auditing, which is considered vital for companies and institutions, because it allows verifying the validity of the data used and the degree of its compliance with standards. Accounting and applicable regulations.